Practical Implementation of Wideband and Wide-Scanning Cylindrically Conformal Phased Array - Xiao, Shiwei; Yang, Shiwen; Zhang, Hangyu; Xiao, Qianshu; Chen, Yikai; Qu, Shi-Wei (IEEE transactions on antennas and propagation, 2019)
A practical implementation of wideband and wide-scanning cylindrically conformal phased array is presented in this communication. First, the design of a dual-polarized planar array is introduced in advance. Then, as a preliminary performance investigation of a conformal phased array, a single-polarized array element counterpart is developed from the dual-polarized planar array with simple modifications. Finally, a conformal array is implemented using the 8 × 8 single-polarized radiating elements that are axially mounted onto a cylindrical surface with a radius of 150 mm. A conformal array prototype is fabricated and measured. The experimental results demonstrate that the array achieves active VSWR less than 3.0 over a bandwidth of 6-18 GHz (3:1), within a wide-scanning range of ±60° in two principal planes. The measured results are in good accordance with the simulations, thus validating the performances of the proposed wideband and wide-scanning cylindrically conformal phased array.